Pengembangan E-modul Berbasis Etnomatematika yang Mengeksplorasi Nilai dan Budaya Islam untuk Siswa SMP - Desmita Ratriana; Riawan Yudi Purwoko; Dita Yuzianah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
This study aims to determine the appropriateness of ethnomatematics-based e-modules that explore Islamic values and culture in terms of validity, practicality, and effectiveness. This type of research is a research and development method using the Borg and Gall model. Through these stages of development, a major product is produced in the form of e-modules based on ethnomatematics that explore Islamic values and culture. Subjects in this study were students of SMP Negeri 4 Purworejo 2019/2020 Academic Year. The instrument used in this study was an assessment sheet by material experts, media experts, cultural experts, atomathematics experts, student questionnaires and evaluation test questions. The results obtained were a feasibility test through a questionnaire conducted by material experts, media experts, cultural experts and ethnomatematics experts meeting valid criteria with an average of 3.63. Ethnomatematics-based e-Modules that explore Islamic values and culture meet practical criteria with an average of 3.11 and show the level of practicality with good criteria. Ethnomatematics-based e-modules that explore the values and culture of Islam meet the effectiveness criteria by giving a very positive response with a percentage of 91% of the learning process and showing the completeness of student learning reaches 92% complete. These data indicate that the e-modules developed in this study are categorized as feasible to use reaching 92% complete. The data shows that the e-modules developed in this study are categorized as suitable for use.